Mathematics Teachers' Encouragement of Their Students' Metacognitive Processes - Wajeeh Daher; Iman Hashash (MDPI AG, 2022)
Researchers have conducted little research into teachers' practices to encourage their students' metacognition. The present research attempted to address this issue quantitatively by suggesting a questionnaire that measured teachers' encouragement of students' planning, monitoring, regulating, and evaluating. We present the results of the validity and reliability of the questionnaire. In addition, using a one-sample t-test, the results of the research revealed "normal", "good", and "very good" levels of teachers' encouragement of their students' metacognitive practices. The present research utilized an independent-sample t-test to investigate the significance of the difference in teachers' metacognitive practices due to gender and to academic qualification. The results indicated that the metacognitive practices for male and female teachers were significantly different in planning and regulating, while the differences were not significant in monitoring and evaluating. In addition, the research results indicated that the participating teachers' practices related to students' metacognitive processes did not differ significantly due to the teachers' academic qualification. When utilizing a one-way ANOVA test to investigate the significance of the difference in teachers' metacognitive practices due to years of experience, this difference was not significant for any of the factors of metacognitive practices.